Infectious diseases amidst a humanitarian crisis in Ukraine: A rising concern. (June 2022) - Essar, Mohammad Yasir; Matiashova, Lolita; Tsagkaris, Christos; Vladychuk, Valeriia; Head, Michael
Abstract: As of the 24th of February 2022, the war in Ukraine has increased the risk for infectious diseases outbreaks in the country and beyond. The disruption of healthcare services, the destruction of critical infrastructure, the displacement of millions of civilians and the crowded living conditions in bunkers pose a formiddable threat to public health. Infections are emphasized due to the low rates of vaccination against COVID-19 and the high prevalence of chronic infections such as Tuberculosis and HIV/AIDS in Ukraine compared to the WHO Europe region. Collaboration between authorities and humanitatian organizations is necessary, in order to strengthen epidemiological surveillance and deploy vital resources that are required for the prevention and the management of infections.